A utilização de madeira nativa para exploração comercial sustentável no setor de construção civil: a possibilidade da Araucaria angustifolia - Ferrari, Andressa Maria Woytowicz (2011)
This research presents an approach on the use of wood as a renewable material in the construction sector, which is derived from sustainable plantations that encourage the use of the native species Araucaria angustifolia. Discusses concepts of minimization of construction materials impacts and of sustainable architecture. Brings references on certification and legalization of wood. Displays forestry and sustainable forest management as alternatives to supply raw materials to the construction sector, providing income to farmers and rescuing the cultivation of a species of environmental and cultural importance very relevant to the south of Brazil. Problematizes legal issues which discourage commercial exploitation of the species, as well as issues related to recovery of legal reserve areas that encourage the use of the species and enable their sustainable management. With the help of technological tools it was possible to confirm the hypothesis of obtaining Araucaria wood in conducted plantings, testing their financial viability and their ability in sequester and store carbon. The softwares used for this purpose promoted the comparison of plantations with the same management plan for the species of pine and Araucaria. These comparison was done because the pine is one of the major exotic cultures found in forest plantations in southern Brazil. The study found, through the use of such softwares, that the Araucaria is a species capable of economic exploitation through their timber products. The results show that the volume of production of Araucaria does not outweigh the pine, but the financial analysis shows that the Araucaria becomes higher than the pine in revenue generation by adding wood products to the estimates of income earned through the sale of its seeds. The results also confirm that the Araucaria has a higher capacity than the pine trees in carbon stock per m3 of timber.